12+c=-2c

Simple and best practice solution for 12+c=-2c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12+c=-2c equation:


Simplifying
12 + c = -2c

Solving
12 + c = -2c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '2c' to each side of the equation.
12 + c + 2c = -2c + 2c

Combine like terms: c + 2c = 3c
12 + 3c = -2c + 2c

Combine like terms: -2c + 2c = 0
12 + 3c = 0

Add '-12' to each side of the equation.
12 + -12 + 3c = 0 + -12

Combine like terms: 12 + -12 = 0
0 + 3c = 0 + -12
3c = 0 + -12

Combine like terms: 0 + -12 = -12
3c = -12

Divide each side by '3'.
c = -4

Simplifying
c = -4

See similar equations:

| -4(x-3)=x | | -16k=-15k-16 | | -4n+5=13 | | -4+5=13 | | 8x/20x=9/20 | | 6x-6+x=4x+8 | | -9x+2.6+(-x)+(-12.8)= | | 2x+9-3x=12 | | z^2+16z+7=0 | | X+3y+3z=10 | | x/x^2=0 | | (Ab+b-c+6)+(3ab-b+c-6)= | | 8a-4(-5a-2)=24a | | 6u+8=21 | | 2y-24=26 | | 1/3s=-2 | | 10-2/5x=-3 | | 5e+6pd+5d-7ed+7= | | 10-2/5x=3 | | 1/2(13f/5 | | 4-1/2v=-4 | | 2.5+-3.5x=-32x+-48 | | 4-1/2v=4 | | 12+4pd-2p+6pd= | | -5w^3-4w^2=7w+16 | | 2.5+-3.5x=-32+-48 | | 8-5n=3.25 | | -3yx+2x+6y-4=0 | | 5x-9=54-4x | | 2x+3y+4x+5x+6x= | | 2x+2x-6=8 | | P+pq-q-p+3pq-3-q+7= |

Equations solver categories